Fingerprint Recognition System(FRS) for the Perak Loan/Scholarship System - Abdullah, JarmatuI Aliah (Universiti Teknologi Petronas, 2006)
Creating a biometric verification system in an energy and area constrained embedded environment is a challenging problem. This paper gives results for using triangulation process to improve performance ofminutiae matching. Triangulation process is the process of aligning the two fingerprints and compares the fingerprint minutiae with minutiae in the database. Human has almost 50 minutiae in their fingerprints. The fingerprint recognition system (FRS) will test the fingerprint and allows the Perak Loan/Scholarship system tobe access when 13 minutiae match with the stored fingerprint data. However, as many data in the database, there are problems ofacquiring the data. The time taken to retrieve data may increase due to this large volume ofdata stored. In a real apphcation, the sensor, the acquisition system and the variation in performance ofthe system over time is very critical. Therefore the system improves the minutiae matching performance by achieving data retrieving in within 3 seconds. Aset of30 fingerprints from 10 individuals were used totest the system. As the result of the proposed approach, the author achieved 2.68 seconds of average fingerprint matching time and 80% ofcorrect fingerprint matching accuracy for FRS.